2019
DOI: 10.7554/elife.42486
|View full text |Cite
|
Sign up to set email alerts
|

Panton–Valentine leucocidin is the key determinant of Staphylococcus aureus pyomyositis in a bacterial GWAS

Abstract: Pyomyositis is a severe bacterial infection of skeletal muscle, commonly affecting children in tropical regions, predominantly caused by Staphylococcus aureus. To understand the contribution of bacterial genomic factors to pyomyositis, we conducted a genome-wide association study of S. aureus cultured from 101 children with pyomyositis and 417 children with asymptomatic nasal carriage attending the Angkor Hospital for Children, Cambodia. We found a strong relationship between bacterial genetic variation and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 58 publications
3
64
0
2
Order By: Relevance
“…Successful applications of mGWAS include identifying genetic determinants of pyomyositis in Staphylococcus aureus (Young et al, 2019) which revealed that the presence of Panton-Valentine leucocidin (PVL) locus increased the odds of pyomyositis. In another study, showed that variations in Streptococcus pneumoniae explain large amounts of the invasiveness potential but have no effect on severity of pneumococcal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Successful applications of mGWAS include identifying genetic determinants of pyomyositis in Staphylococcus aureus (Young et al, 2019) which revealed that the presence of Panton-Valentine leucocidin (PVL) locus increased the odds of pyomyositis. In another study, showed that variations in Streptococcus pneumoniae explain large amounts of the invasiveness potential but have no effect on severity of pneumococcal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing sequencing data available, this is being complemented by genome-wide association studies (GWAS) (Chen and Shapiro 2015;Falush 2016). Several bacterial GWAS have been reported for S. aureus (Alam et al 2014;Laabei et al 2014;Baines et al 2015;Young et al 2019) and other species (Howell et al 2014;Earle et al 2016;Coll et al 2017). These have largely addressed pathogenicity and virulence (Howell et al 2014;Laabei et al 2014;Lees et al 2016Lees et al , 2019, and antibiotic resistance (Alam et al 2014;Desjardins et al 2016;Earle et al 2016;Coll et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate characterization of large numbers of microbial genomes is becoming increasingly important in microbiology. For example, bacterial genome-wide association studies (bGWAS) rely on the sequencing of large numbers of samples to correlate genetic variants to phenotypes such as antibiotic resistance or virulence [1][2][3]. Further examples are phylogenetic analyses and quality assurance in industrial microbiology [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%